THE SWAT MODEL FOR ECO-DRAINAGE SYSTEMCASE STUDY: CIKAPUNDUNG SUB-WATERSHED, WESTJAVA, INDONESIA - P.K Widjokongko; Ramadhani Yanidar; W.Astono; A.D. Astuti; L.Siami (Journal of Synergy Landscape, 2025)
Converting land functions from vacant land to build area could be increased surface water flow and flood. The emergence of slum settlements and land conversion along the riverbanks mark changes in the Cikapundung watershed. The objectives of this study were to investigate the relationship between land use change and the hydrology of the Cikapundung watershed, as well as to offer land use scenarios for reducing surface water flow. The Soil and Water Assessment Tool (SWAT) used to assess the impacts of land use changes. It consists of several stages, namely watershed delineation, formation of a Hydrological Response Unit (HRU), climate data input, running the model, calibration, and validation. The SWAT model can predict the discharge flow with Coefficient of Determination (R2) and Nash-Sutcliffe Efficiency (NSE) values of 0.80 and 0.05 for the calibration phase, and R2 and NSE values of 0.79 and -0.62 for the validation process. Based on SWAT simulation results, the water balance depicts the hydrological analysis of the Cikapundung Sub-watershed, which includes rainfall of 1,518.4 mm/year, surface runoff of 542.7 mm/year, lateral flow of 265.9 mm/year, and base flow of 117,78 mm/year.  The soil and water conservation (SWC) techniques such as reforestation in sub-basin 1, agroforestry in sub-basin 2 and 3, and infiltration wells in sub-basin 4, should be the effective strategy for reducing runoff in the Cikapundung sub-watershed. This scenario has the potential to reduce surface flow by 50.2 percent while increasing lateral flow by 42.5 percent and base flow by 114.3 percent.